Interprofessional education in a community-based setting: An opportunity for interprofessional learning and collaboration - Fatemeh Keshmiri; Tohid Seif Barghi (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: An interprofessional community-based education provides proper situations that learners can be prepared to play their professional responsibilities and team duties in the community. This study aims to assess the effect of interprofessional community-based education on attitudes and performances of learners toward interprofessional collaboration and their readiness for interprofessional learning. MATERIALS AND METHODS: The study is a quasi-experimental design. The learners in six different disciplines, including medicine, pharmacy, nursing, midwifery, public health, and nutrition (n=122) at Shahid Sadoughi University of Medical Sciences were participated in the present study. in the present study, interprofessional education intervention was conducted in two steps. First, the interprofessional learning situation brought learners the familiarity with the concepts of interprofessional collaboration, teamwork, and educational medical content, such as backache, fatty liver, diabetes, and HIV. Second, learners from different disciplines participated in interprofessional teams in community settings. These learners taught people about health-related topics, such as backache, fatty liver, and HIV. Participants filled out the questionnaires before and after interventions. Data were analyzed by Student's t-test and one-way ANOVA in SPSS 16.0 software (SPSS, Inc., Chicago, IL, USA). RESULTS: The present results showed that the scores of learners in readiness for interprofessional learning 3.82 (0.35) versus 4.60 (0.29) (P = 0.001) (P = 0.0001), attitudes to interprofessional teamwork 3.83 (0.40) versus 4.18 (0.30) (P = 0.0001) (P = 0.0001), interprofessional collaboration 7.46 (0.70) versus 8.35 (0.43) (P = 0.001) improved significantly before and after the educational interventions. CONCLUSION: The present results showed that interprofessional community-based education has improved the readiness of the learners for interprofessional learning. Besides, attitude toward teamwork and interprofessional collaboration performance have also been improved from participants' viewpoints.